2016
DOI: 10.3727/096504016x14611963142290
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-15a Inhibits Proliferation and Induces Apoptosis in CNE1 Nasopharyngeal Carcinoma Cells

Abstract: Nasopharyngeal carcinoma (NPC) is a highly metastatic cancer, frequently occurring in Southeast Asia and Southern China. Several microRNAs (miRNAs) have been shown to have an inhibitive effect on NPC, while the effect of miR-15a on NPC remains unclear. Thus, our study aimed to investigate the potential effect of miR-15a on NPC cell proliferation, apoptosis, and possible functional mechanism. Human NPC CNE1 cells were transfected with miR-15a mimics, miR-15a inhibitors, or a control. Afterward, cell viability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Moreover, many miRs have been reported to direct target oncogenes or tumor suppressors, and thus play suppressive or promoting roles in human cancers (10,1214). In recent decade, deregulations of specific miRs have been implicated in NPC development and progression, such as miR-15a, miR-138, miR-214, miR-218, and miR-663b (1519). Yi et al reported that inhibition of miR-663 suppressed the proliferation of NPC CNE1 and 5-8F cells in vitro , and the NPC tumor growth of xenografts in nude mice (19).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many miRs have been reported to direct target oncogenes or tumor suppressors, and thus play suppressive or promoting roles in human cancers (10,1214). In recent decade, deregulations of specific miRs have been implicated in NPC development and progression, such as miR-15a, miR-138, miR-214, miR-218, and miR-663b (1519). Yi et al reported that inhibition of miR-663 suppressed the proliferation of NPC CNE1 and 5-8F cells in vitro , and the NPC tumor growth of xenografts in nude mice (19).…”
Section: Introductionmentioning
confidence: 99%
“…For example, abnormal overexpression of miR-15a-5p was reported to suppress cancer proliferation, induce cell cycle arrest in human HCC cells, and have a specific and negative regulating effect on BDNF (6). In addition, the protein levels of p27, GSK-3beta, Bax, procaspase3, and active caspase 3 were upregulated by the overexpression of miR-15a, which inhibited proliferation and induced apoptosis of CNE1 cells (10). There were other studies that investigated the role of miR-15a in OA.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs), a class of small non-coding RNAs, can directly bind to the 3' untranslated region (UTR) of their target mRNAs, and cause RNA degradation or translation inhibition (7,8). Through mediating the expression of their target genes, miRs are involved in various cellular biological processes, including cell proliferation, differentiation, migration and invasion, as well as tumorigenesis (9)(10)(11). A large number of miRs have been demonstrated to have promoting or suppressive roles in various human cancer types, including cervical cancer, and certain miRs are strongly associated with HPV (12,13).…”
Section: Introductionmentioning
confidence: 99%